Bond market fire sales and turbulence in the Norwegian FX market in March 2020 - Ragna Alstadheim; Kjell Bjørn Nordal; Olav B. Syrstad; Saskia Ter Ellen; May-Iren Walstad Wassås (Norges Bank, 2021)
– The world witnessed a meltdown in financial markets in March 2020 as the Covid-19 pandemic hit the global economy. In this memo we document how the turbulence affected Norwegian financial markets. We describe possible mechanisms behind the stress in the Norwegian foreign exchange and bond markets, and how policy measures were used by Norges Bank to alleviate market frictions.
hdl:11250/2728573
Keywords: 330; Devisenmarkt; Rentenmarkt; Coronavirus; Zentralbank; Geldpolitik; Norwegen